DETERMINAN YANG MEMPENGARUHI PADA KINERJA KARYAWAN PT. VIRTUS FACILITIES SERVICES AREA BANDUNG - Fitriani Fajar; Rommy Mochamad Ramdhani; Santi Maria (STIA Bagasasi, 2022)
Human resources in a company are valuable assets because they can affect the existence of an organization in the future. Each company has different management in creating a good performance for its human resources. Good performance management will realize high-performance productivity in the organization. Many factors that affect employee performance include compensation and a non-physical work environment. Researchers formulate problems on the impact of the determinants on employees to measure performance. This study aims to determine how the determinants (compensation and non-physical work environment) affect employee performance. The research method used is descriptive quantitative which describes the data obtained from PT Virtus Facilities Service Area Bandung. The results of the analysis obtained from the factors that affect performance, by measuring the scale of the indicators are quality, quantity, timeliness, independence, and independence.